URGENSI PEMBENTUKAN LEMBAGA PENEMPATAN ANAK SEMENTARA (LPAS) TERKAIT DENGAN MEKANISME PENAHANAN TERHADAP ANAK OLEH PENUNTUT UMUM (STUDI KASUS DI KEJAKSAAN NEGERI BANGLI) - I Gusti Ngurah Agung Budiarta; I Nengah Susrama (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2023)
Detentions made to ABH must be separated from adults as regulated in Article 3 letter b of the UU SPPA. Detention of ABH based on Article 105 of the UU SPPA is required to be carried out at the LPAS institution. The problem in this study is that Bali Province is one of the regions in Indonesia that does not yet have a LPAS as a support for the enactment of the UU SPPA. Based on the results of research conducted on these problems, it can be concluded that the mechanism for eliminating ABH stems from the Criminal Procedure Code (KUHAP) and the SPPA Law. The general prosecutor of the Bangli District Attorney in this case has not been able to fully implement the provisions in Law Number 11 of 2012 Article 33 paragraph (4) where child detainees should be held in Penitentiary or if there is no Penitentiary, then in accordance with the provisions of Article 33 paragraph (5) can be carried out in Social Welfare Organizing Institutions (LPKS), but in practice children who are in conflict with the law are still kept in detention centers.